KEKERASAN DALAM RUMAH TANGGA DAN PERAN LEMBAGA AGAMA DI BANYUMAS JAWA TENGAH - Umi Muzayanah (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2016)
Domestic violence has sometimes happened in the household. Banyumas district  places as the biggest ten in Central Java province having domestic violence in terms of numbers, especially violence against children and women. This study applies a qualitative approach which aims to examine the underpinning factors caused domestic violence and how the religious institution deals with this issue in Banyumas district. Findings of this research portray that one of the causes of most violence against women is low economic level of the family. The majority cases of domestic violence against women are handled by non-religious organization such as non-governmental organization and an institution formed by the local government. Religious organization has limited roles in dealing with domestic violence, for instance a preventive activity through religious teaching and religious dialog.